Body Weight, Intestinal Morphometry and Cell Proliferation of Broiler Chickens Submitted to Cyclic Heat Stress - Marchini, C.F.P.; Silva, P.L.; Nascimento, M.R.B.M.; Beletti, M.E.; Silva, N.M.; Guimaraes, E.C. (International Journal of Poultry Science, 2011)
To investigate the effects of heat stress on body weight, intestinal length, mucous area, crypt’s depth, villus height and percentage of cells in proliferation activity in male broiler chickens, one hundred birds of Avian Farms strain were housed in cages and divided into two groups, the reared under heat stress and in thermoneutrality. The group reared under heat stress was submitted daily, from 12-13 h, to 38oC from first to 27th day old and 40oC from 28 to 42nd day. The group reared in thermoneutrality was maintained for 24 h in comfort temperature. The body weight of ten birds of each group was obtained weekly from the first until 42nd day old. Each week, five birds from each group were euthanased by cervical dislocation to obtain intestinal length, the mucous area, crypt’s depth, villus height and percentage of cells in proliferation activity. A completely randomized design was used in a factorial schema 6 x 2 (six ages: one, seven, 14, 21, 28 and 42 days and two ambient temperatures: thermoneutral and heat stress). Data were analyzed by analysis of variance and means compared by Tukey test at 5%. The birds stressed by heat presented less crypt depth, mucous area and villus height of duodenum and lower intestinal length at 42 days old. However, heat stress did not influence the percentage of PCNA positive cells, the area of the mucosa, crypt’s depth and villus height in jejunum and ileum.